TOP-DOWN AND BOTTOM-UP CLUSTER INITIATIVES IN EUROPE - MĂDĂLINA MATICIUC (Annals of the University of Petrosani: Economics)
This paper aims central to the dynamics research of clustering processes in various parts of Europe, namely the European Union, in order to identify how come the experience earned here could be used in the process of clustering in the countries of Central and Eastern Europe. In this regard, studies were conducted designed to identifying the main guidelines in clusters conceptualization, discerning clustering processes and their dynamics, in two groups of countries. The first group includes the countries where public policies were those that stimulated the space organizations innovation of business in clusters form. The second group includes countries where private initiative stimulated and maintained the entire process of clustering. These specific paper intents, based on a comparative analysis in the dynamics of clustering conducted in the "top down" and "bottom up" logic, to inspire the entire clustering process in Central and Eastern Europe.